Acoustic extraordinary transmission based on near-zero-index metamaterials. (1st September 2022) - Wu, Guanghua; Li, Zhaoyu; Tao, Meng
Abstract: A new strategy for enhancing sound transmission in a waveguide that contains a narrow slit is proposed. Two metamaterials with near-zero mass density are placed in the waveguide to make the effective mass density of air in the middle region vanish. Both simulation and experimental results demonstrate the effectiveness of the proposed strategy. Due to the wave manipulation characteristics of near-zero metamaterials, sound transmission exhibits high robustness, which is independent of waveguide shape and inserted defects. Finally, Fabry–Pérot-like resonances in the metamaterials-slit system leads to a gain effect for sound transmission. Moreover, applications in acoustic sensing and cloaking are envisioned.